Ciclo de vida organizacional no contexto da responsabilidade social empresarial: o caso da piscicultura sustentável na comunidade do córrego do Macuco-ES - Santos, Rhaiane Maria Andrade (2019)
Through a review of organizations 'life cycle theory studies, this research seeks to understand how organizations' life cycle stages develop within the framework of social corporate social responsibility projects aimed at creating sustainable business in a project sustainable fish farming community in the Córrego do Macuco - ES community, promoted by a forestry company. To underpin this understanding, the discussion is based on the life cycle theory of organizations and the life cycle theory of projects applied to sustainable businesses. Based on this, it is possible to understand the path taken by social income generation projects to become social businesses. To achieve the proposed objective, a case study of the Sustainable Fish Farming project was conducted, a qualitative research, using documentary research and semi-structured interview as data collection techniques. As for the research subjects, eight project members and one person who worked in the management of the social project in the holding company were interviewed during its implementation and monitoring. The collected data were submitted to content analysis, with categories defined a posteriori. The data reveal that the organizations life cycle overlaps with the project life cycle in its different phases. In addition, it was possible to verify various indicators of the phases of birth, growth and maturity in the Sustainable Fish Farming project, even though this is not a traditional organization. However, research has shown that social income generation projects that culminate in sustainable businesses have particularities in their cycle that are not encompassed by the Lester, Parnell and Carraher (2003) model of the organizations' life cycle. This empirical study contributed to the theoretical field of life cycle studies of organizations and, secondarily, also contributes to the area of CSR and NS. At the end, suggestions for future research are indicated.understand how organizations' life cycle stages develop within the framework of social corporate social responsibility projects aimed at creating sustainable business in a project sustainable fish farming community in the Córrego do Macuco - ES community, promoted by a forestry company. To underpin this understanding, the discussion is based on the life cycle theory of organizations and the life cycle theory of projects applied to sustainable businesses. Based on this, it is possible to understand the path taken by social income generation projects to become social businesses. To achieve the proposed objective, a case study of the Sustainable Fish Farming project was conducted, a qualitative research, using documentary research and semi-structured interview as data collection techniques. As for the research subjects, eight project members and one person who worked in the management of the social project in the holding company were interviewed during its implementation and monitoring. The collected data were submitted to content analysis, with categories defined a posteriori. The data reveal that the organizations life cycle overlaps with the project life cycle in its different phases. In addition, it was possible to verify various indicators of the phases of birth, growth and maturity in the Sustainable Fish Farming project, even though this is not a traditional organization. However, research has shown that social income generation projects that culminate in sustainable businesses have particularities in their cycle that are not encompassed by the Lester, Parnell and Carraher (2003) model of the organizations' life cycle. This empirical study contributed to the theoretical field of life cycle studies of organizations and, secondarily, also contributes to the area of CSR and NS. At the end, suggestions for future research are indicated.